Paradigm of Electronic Customer Management - Revankar, Bhargav; Shivashankar, K. (Indian Journal of Marketing, 2010)
In today's world of business and technology we are constantly barraged with a never-ending series of acronyms; a relative recent addition is eCRM. Like many of its predecessors, eCRM which stands for electronic customer relationship management, is a term that is tied to a great deal of hype and confusing messages, this article will attempt to provide a framework for understanding but moreover also establish a framework for success. A commitment to true CRM implies the ability to analyze customer data and to use a combination of financial and customer based metrics for decision-making. These are database (data warehouse) and analytic type capabilities that are not unique to CRM; back office applications such as ERP and MRP require the same types of tools.